Advancements in network-based management systems for enhanced business services - Kukartsev, V.V.; Kravtsov, K.I.; Suprun, P.S.; Gek, D.K.; Pinchuk, I.A. (E3S web of conferences, 2023)
This article explores the advancements in network-based management systems designed to enhance and streamline business services. It focuses on the development of an automated information system tailored to optimize the management of atelier services. This system automates service requests, monitors the quality and quantity of solutions, provides up-to-date service listings and optimizations, generates various reports, and offers department managers a valuable tool for automating routine tasks associated with performance registration and related documentation in their respective departments.